MODEL PEMBELAJARAN AKIDAH AKHLAK DALAM PENGUATAN KARAKTER DITENGAH ARUS KUAT MEDIA SOSIAL - Titing Sulastri; M, Kholis (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2024)
The role of educators in schools is to become the school's identity as a good teacher and role model for students, because teachers have a strong influence on the formation of students' habits when they are in the classroom, school, school environment and society. There is a strong relationship between the implementation of learning by teachers and the achievement of student character. Learning good moral beliefs will have a positive effect on changing students' attitudes and behavior in everyday life. This research is descriptive qualitative research taking place at the Bojongnangka Integrated MTs, Tasikmalaya City. Data collection was carried out by means of observation, interviews and documentation to determine the learning model for moral beliefs in strengthening students' character amidst the strong current of social media. The data analysis uses descriptive techniques through three activity flows, namely data reduction, data presentation, and drawing conclusions.The results of his research show that the model for teaching moral beliefs in strengthening students' character amidst the strong current of social media is as follows: through teaching carried out by Aqidah Akhlak educators using 3 methods: explanation, behavior and attitude. Supporting factors are facilities, syllabus, lesson plans, government programs, vision and mission structure and other religious teachers. The obstacle is the lack of creative learning innovation. The solution is that educators must determine selective topics and teaching media.